Wasting time on the internet - Goldsmith, Kenneth 1961- (Harper Perennial, 2016)
Using clear, readable prose, conceptual artist and poet Kenneth Goldsmith's manifesto shows how our time on the internet is not really wasted but is quite productive and creative as he puts the experience in its proper theoretical and philosophical context. Kenneth Goldsmith wants you to rethink the internet. Many people feel guilty after spending hours watching cat videos or clicking link after link after link. But Goldsmith sees that "wasted" time differently. Unlike old media, the internet demands active engagement--and it's actually making us more social, more creative, even more productive. When Goldsmith, a renowned conceptual artist and poet, introduced a class at the University of Pennsylvania called "Wasting Time on the Internet", he nearly broke the internet. The New Yorker, the Atlantic, the Washington Post, Slate, Vice, Time, CNN, the Telegraph, and many more, ran articles expressing their shock, dismay, and, ultimately, their curiosity. Goldsmith's ideas struck a nerve, because they are brilliantly subversive--and endlessly shareable. In Wasting Time on the Internet, Goldsmith expands upon his provocative insights, contending that our digital lives are remaking human experience. When we're "wasting time", we're actually creating a culture of collaboration. We're reading and writing more--and quite differently. And we're turning concepts of authority and authenticity upside--down. The internet puts us in a state between deep focus and subconscious flow, a state that Goldsmith argues is ideal for creativity. Where that creativity takes us will be one of the stories of the twenty-first century. Wide-ranging, counterintuitive, engrossing, unpredictable--like the internet itself--Wasting Time on the Internet is the manifesto you didn't know you needed -- Provided by publisher
Hier auch später erschienene, unveränderte Nachdrucke
Includes bibliographical references (pages 239-247)
Keywords: Goldsmith, Kenneth -- 1961-; Gesellschaft; Medientheorie; World Wide Web; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; PERFORMING ARTS / Storytelling; SOCIAL SCIENCE / Media Studies; Internet / Social aspects